Attachment styles and empathy in trainee nurses: the mediating and moderating roles of attitudes toward death - Wei, Ting; Guo, Meiyi; Jin, Huanle; Zhang, Bingren (Frontiers in Psychology, 2024)
Aim: To explore the precise role of death attitudes in the relationship between attachment styles and empathy levels among trainee nurses. Design: A cross-sectional study was conducted.: A total of 626 Chinese trainee nurses of different attachment types were enrolled, and their attachment styles, death attitudes, and empathy levels were assessed using the Revised Adult Attachment Scale, the Death Attitude Profile-Revised, and the Jefferson Scale of Empathy-Healthy Professionals, and finally data from 566 participants were included for statistical analysis. Results: We found that in trainee nurses with Secure attachment type, Fear of Death, Approach Acceptance, Escape acceptance, and Neutral Acceptance (-) mediated the relationships between attachment-related Avoidance/Anxiety and their overall empathy levels and all its dimensions; while in the Preoccupied type, only Neutral Acceptance (-) mediated the relationships between attachment-related Avoidance and their overall empathy levels as well as Compassionate care; and in the Fearful type, only Fear of death mediated the relationship between attachment-related Avoidance and Compassionate care. Furthermore, in the Secure type, Neutral acceptance attenuated the negative predictions of attachment-related Avoidance on overall empathy level and Perspective taking. Conclusion: Attitudes towards death played different mediating and moderating roles in the relationship between attachment styles and empathy among trainee nurses with different attachment types. Implications for the profession: In addition to acculturated empathy-specific training, targeted death education for trainee nurses with different attachment types is needed to prevent their compassion fatigue.